Why has UK personal saving collapsed? - Muelbauer, J; Murphy, A (Credit Suisse, 1989)
The UK personal savings ratio has fallen from 13 % in 1981 to 5. 9% in 1987 and to 4.5% in 1988, according to the most recent figures. All the major econometric models for consumption have broken down in the 1980s. The paper considers eight possible explanations of which the following three are empirically important: (a) The increases during the 1980s in the ratios to income of the values of both financial and physical assets. Life~cycle theories of consumption predict that such increases should raise consumption to income ratios. (b) The elimination of aggregate credit rationing resulting from financial liberalsation and the entry of the clearing banks and other institutions into the mortgage market. This has been accompanied by easier credit terms applied by lenders to individual borrowers. The paper examines theoretically and empirically the consequences of a falling share of aggregate consumption accounted for by credit constrained households as well as of an increase in the effective fungibility of illiquid assets. (c) A reduction in uncertainty, especially of real income growth, in what has been, after the shocks of 1979-81 and until recently, one of the longer and steadier expansions in post-war history. An important feature of this research is the systematic modelling of price and interest rate effects, and of credit constraints. This yields new insights into the role of monetary policy in influencing expenditure. This is particularly relevant now, when there is much concern over the effect of high interest rates in slowing the consumer boom.